Efektivitas Program Baznas dalam Pengentasan Kemiskinan di Purbalingga - Masriqh, Achyani Aniyk; Suyuti, Muh Hikamudin (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
Poverty is one of the complex social problems that requires sustainable handling. The National Amil Zakat Agency (BAZNAS) acts as an institution that distributes zakat, infaq, and alms funds to help the poor through various empowerment programs. This study aims to analyze the effectiveness of BAZNAS programs in poverty reduction in Purbalingga Regency, especially in the aspect of improving the welfare of beneficiaries. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation studies. The data obtained were analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The results showed that BAZNAS programs, such as business capital assistance, education scholarships, and compensation for the poor and dhuafa, have a positive impact on improving community welfare. However, their effectiveness still faces several obstacles, such as budget limitations, lack of business assistance, and low community participation in the programs provided. In conclusion, the BAZNAS program in Purbalingga is quite effective in helping to reduce poverty, but improvements still need to be made in terms of fund management, synergy with local government, and optimization of assistance to beneficiaries so that the results are more sustainable.